2013
DOI: 10.1007/978-3-319-03590-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Interactive MRI Segmentation for Subject-Specific Modelling of the Tongue

Abstract: Subject-Specific biomechanical modelling of the human tongue is beneficial for investigating the inter-subject variability in the physiology of the speech, chewing and swallowing. Delineation of the tongue tissue from MRI is essential for modelling, but still remains a challenge due to the lack of definitive boundary features. In this paper, we propose a minimally interactive inter-subject mesh-to-image registration scheme to tackle 3D segmentation of the tongue from MR volumes. An exemplar expert-delineated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Harandi et al . [51, 52] repeated manual segmentation of the tongue on a high-resolution MRI, and reported that the volume overlap index between different manual segmentations was 91% (equivalently DSC of 0.91). We expect slightly lower volume overlap in our case as we used cine-MRI of which image quality is poorer than high-resolution MRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Harandi et al . [51, 52] repeated manual segmentation of the tongue on a high-resolution MRI, and reported that the volume overlap index between different manual segmentations was 91% (equivalently DSC of 0.91). We expect slightly lower volume overlap in our case as we used cine-MRI of which image quality is poorer than high-resolution MRI.…”
Section: Discussionmentioning
confidence: 99%
“…We expect slightly lower volume overlap in our case as we used cine-MRI of which image quality is poorer than high-resolution MRI. Although there exists uncertainty in manual segmentation, the variability of the expert’s manual segmentation of the tongue is not high and is considered as reasonable gold standard [51, 52]. Therefore, DSC of around 0.91 or higher is considered acceptable in our experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation